Stress induced half-metallicity in surface defected germanium nanowires - Sk, Mahasin Alam (2013)
Germanium nanowires (GeNWs) with single, double, quadruple and octuple surface dangling bonds (SDBs) are investigated using density-functional-theory calculations. We show that single SDB defected GeNWs remain semiconducting as their non-defected form while double or multiple SDB defects result in either semiconducting or metallic GeNWs, depending on the defect's locations on the surface. More importantly, we show that the electronic properties of surface defected GeNWs can also be fine-tuned by applying tensile and compressive strains. Upon the right loading, the surface defected GeNWs become half-metallic. In addition, we determine that the surface defected GeNWs can be classified into three classes: (1) GeNWs with zero magnetic moment, which are either metallic or semiconducting; (2) GeNWs with net magnetic moments equal to the number of SDBs, which are semiconducting with distinct spin-up and spin-down configurations; and (3) GeNWs with net magnetic moments significantly lower than the number of SDBs. We also find that only the defected GeNWs that fall under (3) are potentially half-metallic. Our results predict that half-metallic GeNWs can be obtained via engineering of the surface defects and the structures without the presence of impurity dopants.